Biodegradable polymer (PLGA) coatings featuring cinnamaldehyde and carvacrol mitigate biofilm formation - Zodrow, Katherine R (Langmuir : the ACS journal of surfaces and colloids, 2012)
Biofilm-associated infections are one of the leading causes of death in the United States. Although infections may be treated with antibiotics, the overuse of antibiotics has led to the spread of antibiotic resistance. Many natural antimicrobial compounds derived from edible plants are safe for human use and target bacteria nonspecifically. Therefore, they may impair biofilm formation with less evolutionary pressure on pathogens. Here, we explore the use of two natural antimicrobial compounds, cinnamaldehyde (CA, from cinnamon) and carvacrol (CARV, from oregano), for biofilm prevention. We have fabricated and characterized films that incorporate CA and CARV into the biodegradable, FDA-approved polymer poly(lactic-co-glycolic acid), PLGA. The addition of CA and CARV to PLGA films not only adds antimicrobial activity but also changes the surface properties of the films, making them more hydrophilic and therefore more resistant to bacterial attachment. An addition of 0.1% CA to a PLGA film significantly impairs biofilm development by Staphylococcus aureus, and 0.1% CARV in PLGA significantly decreases biofilm formation by both Escherichia coli and S. aureus. Pseudomonas aeruginosa, which is less susceptible to CA and CARV, was not affected by the addition of 0.1% CA or CARV to the PLGA coatings; however, P. aeruginosa biofilm was significantly reduced by 1.0% CA. These results indicate that both CA and CARV could potentially be used in low concentrations as natural additives in polymer coatings for indwelling devices to delay colonization by bacteria